Acoustic borehole logging of MeBo sediment core GeoB23231-1 - Tim Freudenthal (PANGAEA, 2020)
Logging was performed with the sea floor drill rig MARUM-MeBo200 in a borehole drilled with a 103 mm diameter bit. The 1343 Slimhole Memory Acoustic instrument developed by ANTARES Datasystems GmbH was used. The probe consists of 1 transmitter and two receivers in 0.9 and 1.0 m distance, respectively. Sound velocity in the formation was calculated from the time difference of signal arrival at both receivers using the waveform processing module of the Antares software GeoBase 6.22.1. Values with a semblance quality of less than 90% were discarded. The vertical resolution is about 10 cm. The accuracy is better than 10 m/s.